Measurement System Analysis Using Repeatability and Reproducibility Techniques - Norizan Mohamed; Yamene Davahran (Program Studi Statistika Unisba, 2006)
To monitor and improve any manufacturing process in quality control, it is important to measure thecause of the attribute for that process. The quality of measurement data depends on the repeatedmeasurements obtained through measurement systems which will operate at a given condition. Thisstudy uses a type of statistical quality control technique called Repeatability and Reproducibility(R&R) to determine how much of the process variation is caused by the variation of the measurementsystem that is being used. The two types of charts that were used for this study were the ANOVAchart and the Mean & Average chart.